2010
DOI: 10.1038/gene.2009.106
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype 4 of the multiple sclerosis-associated interleukin-7 receptor alpha gene influences the frequency of recent thymic emigrants

Abstract: The receptor for the homeostatic T cell cytokine interleukin-7 (IL-7Ra) has recently shown genetic association to multiple sclerosis (MS). To investigate the functional contribution of IL-7Ra polymorphisms to the pathogenesis of MS, we correlated the IL-7Ra haplotypes with different T cell parameters in a group of MS patients and healthy controls. We show that carriers of one of the four IL-7Ra haplotypes (Hap4) show a higher expression of IL-7Ra (CD127) on their CD4þ T cells, compared with noncarriers (P ¼ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…In Caucasians, haplotype-4 has been associated with increased expression of IL-7Ra on T-cells and an increased percentage of CD31 þ naïve T-cells in both patients with multiple sclerosis and controls. 57 This haplotype has also been associated with reduced upregulation of IL-7Ra measured in whole blood in response to interferon-b stimulation as compared with non-haplotype-4 carriers. 58 The relevance of these haplotype-4-associated immunophenotypes in influencing the time to CD4 T-cell 4500 cells ml À1 in Africans carrying the minor G-allele at rs3194051 is currently unknown, but it is unlikely to be related to differences in the levels of sIL-7Ra.…”
Section: Discussionmentioning
confidence: 96%
“…In Caucasians, haplotype-4 has been associated with increased expression of IL-7Ra on T-cells and an increased percentage of CD31 þ naïve T-cells in both patients with multiple sclerosis and controls. 57 This haplotype has also been associated with reduced upregulation of IL-7Ra measured in whole blood in response to interferon-b stimulation as compared with non-haplotype-4 carriers. 58 The relevance of these haplotype-4-associated immunophenotypes in influencing the time to CD4 T-cell 4500 cells ml À1 in Africans carrying the minor G-allele at rs3194051 is currently unknown, but it is unlikely to be related to differences in the levels of sIL-7Ra.…”
Section: Discussionmentioning
confidence: 96%
“…The variants that result in Omenn syndrome show severe loss of function, whereas the variant associated with common autoimmune disease alters splicing efficiency, creating a soluble competitive antagonist form of the receptor (Gregory et al 2007). This reduction in available IL-7 in turn reduces thymic output of T cells (Broux et al 2010), replicating on a less severe form the immunological defect present in Omenn syndrome. Similarly, the gain-of-function PTPN22 allele associated with multiple autoimmune diseases results in a reduction in T-cell receptor (TCR) signaling (Smerdel et al 2004;Vang et al 2005), and may therefore also contribute to partial immunodeficiency.…”
Section: Common Autoimmune Risk Variantsmentioning
confidence: 99%
“…Regarding the functional effects of IL7RA haplotypes beyond altered sIL-7RA levels previous studies have shown differences between haplotype 2 and non-haplotype 2 carriers with respect to the frequency of recent thymic emigrants 11 and response of CD4 + lymphocytes to interferon beta 12 . The functional effects on T cell stimulation of haplotype 2, which has not been found to related to MS risk, is thought to arise from differences in the genomic sequences within the promoter region of the IL7RA locus, which are also tagged by the SNPs used to define haplotypes.…”
Section: Introductionmentioning
confidence: 99%